A feminist analysis of child neglect cases from the Brazilian Superior Court of Justice - Flavia Portella Püschel (Revista Direito GV)
Abstract This article analyzes the opinions of judges of the Brazilian Superior Court of Justice (STJ) in child neglect cases from a feminist perspective by “asking the woman question” to identify implicit male bias in legal concepts and standards that are apparently gender neutral. Several sexist arguments can be found both in opinions against awarding damages for child neglect and in opinions in favor of it. Sexist bias is shown in the disregard of legal doctrine, as well as of the ambivalent character of family relations and their hierarchical structure. This bias is further expressed in the devaluation of women’s interests and life experiences, stereotyping, problems of logical reasoning as well as in the disregard of statutory rules. The article concludes that the STJ was unable to take into account the point of view of women and the circumstances in which child neglect actually takes place in Brazilian society today. The court developed a concept of harm that, although apparently gender neutral, is based on discriminatory reasons and has greater negative impact on women than on men.